Bingkisan hadiah pencetus keberlangsungan hubungan diplomatik pada zaman Kesultanan Melayu - Noor Muhammad, Salmah Jan (Institute of the Malay World and Civilisation, Universiti Kebangsaan Malaysia, 2014)
Gift parcels are the mechanism used by a government to trigger diplomatic relations with foreign governments. In the Malay Sultanate epoch, besides to establish diplomatic relations, the gift is intended to strengthen the sovereignty, cast a political power, extend the influence of custom and culture, as well as spread the religion that became the philosophy of society at that time. Diversity in giving gifts is a result of a combination of thoughts of the king and his officials to create, perpetuate, and strengthen diplomatic relations. It is the practice used by a Malay government, as an ‘antidote’ to impress the Malay rulers who represent other Malay governments or other Western governments, as a ‘recepient’ government to receive and maintain those relationships. This article discusses the diversity of the gift used by a government in the success of diplomatic relations, in addition to discuss the motives of the gift awarded by focusing on Malay manuscripts as the main discourse.